Incomplete humeral condylar fracture in two English Pointer dogs - Gnudi, G.; Martini, F. M.; Zanichelli, S.; Volta, A.; Bertoni, G.; Del Bue, M.; Borghetti, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Incomplete humeral condylar fracture was diagnosed by means of radiology, CT, scintigraphy, arthroscopy and bone biopsy in two English Pointer dogs. In both cases an acute thoracic limb lameness, unrelated to a known episode of major trauma, was observed. Incomplete humeral condylar fracture, mainly described in the Spaniel breeds, has been recently diagnosed in Labrador retrievers, Rottweiler, German Wachtel and other breeds. The pathogenesis of the condition is still unknown, but incomplete ossification of the humeral condyle and mechanical stress, alone or associated, have to be considered. However, our clinical and histopathological data lead us to believe that in Pointers, high performance dogs, the mechanical stress can assume a critical ethiopathogenetic role.
Keywords: Humeral condyle; incomplete fracture; Pointer; dog